UPAYA YANG DILAKUKAN OLEH SATPAM TERHADAP HILANGNYA BARANG PERUSAHAAN PIHAK KETIGA SEBAGAI PENGGUNA JASA PT PUTRA TIDAR PERKASA - Raharusun , Janir Francis; Ukas, Ukas (LPPM Universitas Putera Batam, 2023)
Many cases of loss of company goods are no longer new to security forces such as security guards. Starting from a loss with a relatively low amount of loss to a loss with a relatively high amount of loss. Based on the description of the background that the author has described in CHAPTER I, the purpose of the research is to find out the responsibilities carried out by security guards at PT. Putra Tidar is mighty in resolving the loss of goods that occurred at a third company, namely Nagoya Hil2. What witnesses did Nagoya hil Mall to the loss of company The research method that the author uses in this type of research is empirical juridical. The nature of the research in this paper is descriptive research, which describes the problems that occur in the field in written form. The results of the research that will be described or described are the results of the first, How the Responsibilities of PT. Putra tidar mighty in solving problems of lost goods that occur in third party companies; second, What the sanctions are given by third parties for negligence by security guards on reports of lost goods at third party companies.